Establishment of Genome Editing in Symbiodinium - Gavin, Lucy (2025)
Symbiodinium microadriaticum is a symbiotic algae that is crucial to coral reef ecosystems. It plays a vital role in coral health through its symbiosis with corals, supplying them with nutrients via photosynthesis. However, environmental stressors such as increasing sea temperatures and overexposure to sunlight have led to widespread coral bleaching, threatening reef ecosystems. This project explored the potential of applying CRISPR-Cas9 gene-editing technology to S. microadriaticum. This technique could be a tool for enhancing its resilience to such stressors. The project focused on several key objectives: determining whether D-amino acids, specifically D-alanine, could serve as practical selectable markers, optimising transformation conditions using Lonza electroporation, and inserting foreign genes into the Symbiodinium genome.